Analysis of Geometrically Consistent Schemes with Finite Range Interaction (Communications in Computational Physics, 2017)
We analyze the geometrically consistent schemes proposed by E. Lu andYang [6] for one-dimensional problem with finite range interaction. The existence ofthe reconstruction coefficients is proved, and optimal error estimate is derived undersharp stability condition. Numerical experiments are performed to confirm the theoreticalresults.